(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
It is known that the concept of a sentence is inextricably linked with the concept of person, number, and time. Also for nominative sentences this idea should be applied. In existing literature, intonation completeness is shown as the basis for the formation of a word or phrase in a sentence